Memasyarakatkan Pendidikan melalui Kearifan Budaya Lokal - Neni Nadiroti Muslihah; Ejen Jenal Mutaqin; Widdy Sukma Nugraha; Abdul Hakim (Jurnal Pekemas, 2019)
This community service aims to provide insight into knowledge about education through local cultural wisdom in Cigalontang Tasikmalaya District, by providing insight into knowledge about the importance of education from primary to secondary education. The problems that arise in these areas are resolved in three stages of activities, namely preparation, implementation and evaluation. The results of the service activities show the level of success with an indication of the similarity in the mindset of educators in the Cigalontang District environment, a positive response from the community service participants related to an understanding of education that must synergize with local life in the local area and most of the community has understood the concept of local cultural development. as an icon of community growth.